Can the current environmental tax rate promote green technology innovation? - Evidence from China’s resource-based industries - Wang, Yan; Yu, Lihong (Journal of cleaner production, 2021)
The exploitation and utilization of mineral resources can induce externality problems. An environmental tax rate directly affects pollution reduction results and the green production of resources industries. Considering the higher pollution emission of resource-based industries, China’s environmental tax rate is too low to fully compensate for externality and it impedes technological innovation. This paper firstly calculates the optimal tax rate of China’s resource-based industries, based on the statistical relationship between environmental tax rates and pollution emissions. Then, the efficiency of green technology innovation is evaluated. The results show that environmental externalities have a depressing effect on green technology innovation. Furthermore, this paper constructs a threshold effect model of the impact of the optimal environmental tax rate on green technology efficiency. It turns out that the air pollution tax rate has a non-linear effect on green technology innovation, and the implementation standard of tax is lower than the optimal tax rate. In addition, the water pollution tax has no optimal level and has an uncertain impact on green innovation. Therefore, China should gradually increase the environmental tax rate, in order to achieve pollution reduction and technological innovation. •Optimal Environmental tax should be commensurate with the level of emissions.•China’s environmental tax rate is too low to compensate for externality.•Environmental externality has a depressing effect on green technology innovation.•The implementation standard of tax is lower than the optimal tax rate.•The air pollution tax rate has a non-linear effect on green technology innovation.